C Insulin resistance impairs angiogenic progenitor cell function and delays endothelial repair following vascular injury. (9th June 2011) - Kahn, M B; Yuldasheva, N; Cubbon, R; Surr, J; Rashid, S; Viswambharan, H; Imrie, H; Abbas, A; Rajwani, A; Gage, M; Kearney, M T; Wheatcroft, S
Abstract : Introduction: Insulin-resistance, the primary metabolic abnormality underpinning type-2-diabetes mellitus (T2DM) and obesity, is an important risk factor for the development of atherosclerotic cardiovascular disease. Circulating-angiogenic-progenitor-cells (APCs) participate in endothelial-repair following arterial injury. Type-2 diabetes is associated with fewer circulating APCs, APC dysfunction and impaired endothelial-repair. We set out to determine whether insulin-resistance per se adversely affects APCs and endothelial-regeneration. Research Design and Methods: We quantified APCs and assessed APC-mobilisation and function in mice hemizygous for knockout of the insulin receptor (IRKO) and wild-type (WT) littermate controls. Endothelial-regeneration following femoral artery wire-injury was also quantified at time intervals after denudation and following APC transfusion. Results: The metabolic phenotype of IRKO mice was consistent with compensated insulin resistance, with hyperinsulinaemia after a glucose challenge but a normal blood glucose response to a glucose tolerance test. IRKO mice had fewer circulating Sca-1+/Flk-1+ APCs than WT mice at baseline. Culture of mononuclear-cells demonstrated that IRKO mice had fewer APCs in peripheral-blood, but not in bone-marrow or spleen, suggestive of a mobilisation defect. Defective VEGF-stimulated APC mobilisation was confirmed in IRKO mice, consistent with reduced eNOS expression in bone marrow and impaired vascular eNOS activity. Paracrine-angiogenic-activity of APCs from IRKO mice was impaired compared to those from WT animals. Endothelial-regeneration of the femoral artery following denuding wire-injury was delayed in IRKO mice compared to WT (re-endothelialised area 35.8±4.8% vs 66.6±5.2% at day 5 following injury and 35.6±4.8% vs 59.8±6.6% at day 7; P<0.05) (Abstract C Figure 1A ). Transfusion of mononuclear-cells from WT mice normalised the impaired endothelial-regeneration in IRKO mice (57±4% vs 25±5%; p<0.002). Transfusion of c-kit+ bone-marrow cells from WT mice also restored endothelial-regeneration in IRKO mice (62±2% vs 25±5%; p<0.002). However, transfusion of c-kit+ cells from IRKO mice was less effective at improving endothelial-repair (62±2% vs 45±4%; p<0.02) (Abstract C Figure 1B ). Conclusions: Insulin-resistance impairs APC function and delays endothelial-regeneration following arterial injury. These findings support the hypothesis that insulin-resistance per se is sufficient to jeopardise endogenous vascular repair. Defective endothelial-repair may be normalised by transfusion of APCs from insulin-sensitive animals but not from insulin-resistant animals. These data may have important implications for the development of therapeutic strategies for insulin-resistance associated cardiovascular disease.